Total glucosides of paeony for rheumatoid arthritis: a protocol for a systematic review - Jing Luo; Guo-Yan Yang; Di-Er Jin; Ying-Ze Zhang; Jian-Ming Wang; Wei-Ping Kong; Qing-Wen Tao (BMJ Open)
Introduction Total glucosides of paeony (TGP) is a natural plant extract, which is widely used in China for treating rheumatoid arthritis (RA). Many relevant randomised controlled trials (RCTs) of TGP for RA are available, but they have not been systematically reviewed. This systematic review aims to examine the effectiveness and safety of TGP in patients with RA.Methods and analyses We will search for RCTs of TGP in the treatment of RA, performed up until February 2016, in PubMed, Embase, Cochrane Central Register of Controlled Trials, and four Chinese databases (Chinese Biomedical Database, China National Knowledge Infrastructure, Wanfang Database and Chinese Scientific Journal Database). Trial registers and reference lists of retrieved articles will also be searched to identify potential articles. RCTs comparing TGP with placebo, no treatment, or disease-modifying antirheumatic drugs for patients with RA will be retrieved. The primary outcomes will be disease improvement and disease remission. The secondary outcomes will be surrogate outcomes, symptoms, adverse effects, and quality of life. Two reviewers will independently extract data on participants, interventions, comparisons, outcomes, etc. The methodological quality of each included study will be evaluated using the Cochrane risk of bias tool, and the strength of evidence on prespecified outcomes will be assessed in accordance with the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Review Manager 5.3 software will be used for data analyses. Meta-analyses will be performed if the data are sufficiently homogeneous, both statistically and clinically. Possible publication bias will also be checked using funnel plots once the number of included studies is sufficient.Ethics and dissemination Ethics approval is not required, as this study will not involve patients. The results of this study will be submitted to a peer-reviewed journal for publication, to inform both clinical practice and further research.Trial registration number CRD42015026345.